FINANCIAL PERFORMANCE ANALYSIS SURROUNDING INDONESIAN INITIAL PUBLIC OFFERINGS - Elok Sri Utami, Marmono Singgih, Tatang Ari Gumanti & Selfi Dewi Qomariyah (International Journal of Research Science and Management, 2020)
One of the ways to find out the performance of company making Initial Public Offering (IPO) is through the financial performance analysis. The analysis would help investors prior to deciding to buy the stocks of the company. Financial ratios are a common tool used in making financial statement analysis. This study aims to analyze whether the companies’ financial performance improves after the IPO. This research is quantitative research using secondary data. The sample consists of 59 companies’ making IPOs on the Indonesia Stock Exchange from 2010 to 2014. Results indicate that only Current Ratio increases significantly over three years after the IPO. The other ratios, i.e., Debt to Asset Ratio, Debt to Equity Ratio, Total Asset Turnover, Net Profit Margin and Return on Equity decrease. Overall, the financial performance of the companies tends to worsen, except for liquidity ratio.